The phenomenon of social deviant behavior of adolescents addicted to Komix cough syrup Sumpiuh District, Banyumas - Arif Sobirin Wibowo; Paulus Robert Tuerah; Ida Bagus Weda Wigena (Harmoni Sosial: Jurnal Pendidikan IPS, 2021)
The most dangerous juvenile delinquency is the abuse of drugs and illegal drugs and their content, which can lead to diseases that attack organs in the human body to addiction that leads to death. This study aims to determine the phenomenon of adolescent social deviant behavior and the causes and reasons why adolescents become addicted to Komix cough syrup. The subjects of this study were teenagers, especially school-age children, who used Komix cough syrup in amounts beyond the dose that caused addiction, located in Sumpiuh District Banyumas Regency. This study uses a phenomenological research design because it examines the phenomenon of a group of teenagers, namely the use of Komix cough syrup. Data collection techniques and tools used were observation, in-depth interviews, and documentation to collect the necessary data. Data analysis is carried out continuously until complete so that the data is saturated. The results of this study show that problems in the family can cause moral degradation due to a lack of parental supervision and guidance so that social deviations occur, namely the use of cough syrup in large quantities, which causes addiction. The effects of pleasure that they feel after drinking CMC are dizziness, the body feeling light, can forget for a moment the problems that exist, and being sleepy but cannot sleep. Another effect is that it can bring out the original nature of the drinker.